The electronic invoice in the police administration towards a vision of the public administration (2020)
One of the biggest challenges facing companies in Colombia is to take advantage of the use of electronic invoicing, an alternative billing document that must be approved by Dian, which is more than a means of inspection, the new language of digital business documentation, language universal electronic document exchange that eliminates communication barriers, optimizes time, improves process efficiency, and must also comply with the legal and regulatory requirements for traditional paper invoices. Colombia is one of the countries that is in the process of implementing this new technology for issuing invoices, it is not just dematerializing the paper, it is complying with the standards that have been modified and evaluated in the course of the last few years in accordance to other models of countries that have already been invoicing electronically, such as Peru and Mexico. An evolution of the legal framework, where it was thought to be a new topic but which has been discussed since 1995, passing through modifications in 1999, 2005, 2007, 2008, 2016, 2018 and finally 2019 with resolution 001122 of the February 15, 2019 of the DIAN national customs and taxes department where it enables natural persons, legal entities and other subjects who have voluntarily chosen to be electronic invoices. The Colombian National Police must take advantage of this new system, in which it has not carried out the due process of implementation.